Conversation Analysis of Interruption Found In The Indonesia Lawyers Club - Diana Rahma Putri; Ridwan Hanafiah; Muhizar Muchtar (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This thesis is a study about types of interruption and functions of interruption in a television talk show named Indonesia Lawyers Club. This study aims to identify the types of interruption found in the Indonesia Lawyers Club. The main theory used in supporting this study is a theory of types of interruption proposed by Ferguson (1977). In conducting this study, the researcher used a descriptive qualitative method. The results of this study found that there are four types of interruption found in the talk show. They are simple interruption (SI), overlap interruption (OI), Butting-in interruption (BI) and silent interruption (SLI). OI is the most dominant types of interruption found in the data. There are 9 occurrences of OI (36%), 8 occurrences of SI (32%), 5 occurrences of BI (20%) and 3 occurrences of SLI (12%).